Parliamentary democracy in Bangladesh: an evaluation of the parliament during 1996-2009 - Moniruzzaman, Md. (Routledge, 2009)
This study of three parliaments in Bangladesh during 1991–2006 argues that parliament has failed to become the centre of political and legislative activities. This is mainly because the ruling parties deliberately bypass parliament, while the opposition deserts it. The parliament has been dysfunctional for more than half of its tenure. For the short periods it has been active, its business sessions were devoted more to party political bickering than legislative activity. Due to the opposition boycott, the ruling party’s negligence and the absenteeism of ordinary members, the standing committees of the parliaments were less effective, and parliamentary accountability of government was lacking.